Red Saxony : election battles and the spectre of democracy in Germany, 1860-1918 - Retallack, James N. 1955- (Oxford University Press, 2017)
Red Saxony throws new light on the reciprocal relationship between political modernization and authoritarianism in Germany over the span of six decades. Election battles were fought so fiercely in Imperial Germany because they reflected two kinds of democratization. Social democratization could not be stopped, but political democratization was opposed by many members of the German bourgeoisie. Frightened by the electoral success of the Social Democrats after 1871, anti-democrats deployed many strategies that flew in the face of electoral fairness. They battled socialists, liberals, and Jews at election time, but they also strove to rewrite the electoral rules of the game. Using a regional lens to rethink older assumptions about Germany's changing political culture, this volume focuses as much on contemporary Germans' perceptions of electoral fairness as on their experiences of voting. It devotes special attention to various semi-democratic voting systems whereby a general and equal suffrage (for the Reichstag) was combined with limited and unequal ones for local and regional parliaments. For the first time, democratization at all three tiers of governance and their reciprocal effects are considered together.